Pengaruh Motivasi Kerja, Kepemimpinan Ketua STMIK Banjarbaru, Dan Lingkungan Kerja Terhadap Kinerja Dosen Dan Karyawan Pada STIMIK Banjarbaru. - Chandra Ayu Septiawati; Chandra Alief (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
Based on the evaluation results of the annual operational plan at the STMIK Banjarbaru institution, there are several objectives that have not been achieved. Some of the factors that cause employees are not aware of their obligations so that work is neglected, there is no significant difference in treatment between high-achieving and under-performing employees so that employees are not motivated to carry out their duties, and communication between leaders and subordinates is not going well. For lecturers, there is a slightly different treatment due to different workloads. The work environment for lecturers is not limited to fellow lecturers or employees but also includes direct interaction with students, with a higher intensity. The main task of a lecturer is to teach in accordance with the total credit load given by the campus, besides that the lecturer also still has to do research and community service in accordance with the tri dharma of higher education. Direct communication between lecturers and leaders rarely occurs outside of work meetings. This study aims to determine whether there is a relationship between work environment, work motivation, and leadership style of the head of STMIK Banjarbaru on the performance of lecturers and employees. The research method used is a quantitative method with explanatory, associative and correlational levels. The approach used is descriptive analysis and survey, using a questionnaire as a means of collecting data. The sample used in this study were 31 respondents divided into 20 lecturers and 11 employees. From a total population of 103 people (lecturers and employees). Data analysis using multiple linear regression. The results of the analysis show that the influence of the work environment is not significant on lecturer performance and employee performance, either partially or simultaneously. Work motivation partially has no significant effect on lecturer performance, but has a significant effect on employee performance so that simultaneously, work motivation does not have a significant effect on lecturer and employee performance. The leadership style of the chairman of STMIK Banjarbaru partially has a significant effect on the performance of the lecturers, but does not significantly affect the performance of employees. Simultaneously, the leadership style of the Head of STMIK Banjarbaru has no significant effect on the performance of lecturers and employees.